Case Study: PPUPIK Mooghurt Team's Marketing Capabilities, Department of Biology, Faculty of Mathematics and Natural Sciences, UNP - Elsa Badriyya; S. Syamsurizal; Linda Advinda; Resti Fevria (Pelita Eksakta, 2020)
PPUPIK Mooghurt is a business unit that is part of the Entrepreneurship Unit of the Student Association majoring in Biology, FMIPA UNP. To improve the performance of the PPUPIK Mooghurt business unit, a more reliable marketing strategy is needed. The purpose of PKM PPUPIK Mooghurt: to find out the marketing capability of the KWU HMJ Biology FMIPA UNP unit team and offer solutions to their problems. The marketing ability of the PPUPIK Mooghurt team in general has not been satisfactory, so solutions are given to carry out training and socialize mooghurt products to the public. The results obtained were an increase in marketing capabilities for the PPUPIK Mooghurt team, and the product became better known in the community because teachers were also able to disseminate information to their students.